ANALISIS PARTISIPASI POLITIK PEREMPUAN DI INDONESIA: FAKTOR PENGHAMBAT DAN PENDORONG - Kahpi, Mhd. Latip; Harahap, Asriana (Jurnal Kajian Gender dan Anak, 2024)
This research is entitled "Analysis of Women's Political Participation in Indonesia: Inhibiting and Encouraging Factors" and aims to understand the dynamics of women's political participation in the Indonesian context. Using a qualitative approach, this research explores the factors that hinder and encourage women's involvement in politics. Data collection methods include in-depth interviews with women active in politics, leaders of civil society organizations, academics and political observers, as well as analysis of documents and related literature. The research results identified several main inhibiting factors, including the patriarchal culture that is still dominant, lack of political education, structural obstacles within political parties, the double burden experienced by women, and political violence and intimidation. Patriarchal culture places women in traditional roles that limit their participation in the public sphere, while inadequate political education hinders their understanding and involvement in the political process. Structural barriers within political parties also prevent women from achieving leadership positions, and the double burden of being a housewife and a worker makes it difficult for women to participate fully in politics. Apart from that, violence and intimidation against women involved in politics adds to the challenges that must be faced. On the other hand, this research also found several significant driving factors. Affirmative policies, such as gender quotas in political parties and parliament, provide greater opportunities for women to become involved in politics. Increasing political education and gender awareness in society helps build a stronger foundation for women's political participation. Support from non-governmental organizations focused on women's empowerment also plays an important role in strengthening women's capacity and motivation in politics. More inclusive social and cultural change, as well as networks of support and mentorship, are helping women to overcome barriers and participate more actively in politics. This research concludes that although there are many challenges that hinder women's political participation in Indonesia, there are also many motivating factors that can be utilized to increase women's involvement in politics. By continuing to strengthen support for women's political participation and overcome existing barriers, Indonesia can achieve greater gender equality in politics and create a more inclusive and just political environment for all citizens. Penelitian ini berjudul "Analisis Partisipasi Politik Perempuan di Indonesia: Faktor Penghambat dan Pendorong" dan bertujuan untuk memahami dinamika partisipasi politik perempuan dalam konteks Indonesia. Dengan menggunakan pendekatan kualitatif, penelitian ini mengeksplorasi faktor-faktor yang menghambat dan mendorong keterlibatan perempuan dalam politik. Metode pengumpulan data mencakup wawancara mendalam dengan perempuan yang aktif dalam politik, pemimpin organisasi masyarakat sipil, akademisi, dan pengamat politik, serta analisis dokumen dan literatur terkait. Hasil penelitian mengidentifikasi beberapa faktor penghambat utama, termasuk budaya patriarki yang masih dominan, kurangnya pendidikan politik, hambatan struktural dalam partai politik, beban ganda yang dialami perempuan, serta kekerasan dan intimidasi politik. Budaya patriarki menempatkan perempuan dalam peran tradisional yang membatasi partisipasi mereka di ranah publik, sementara pendidikan politik yang kurang memadai menghalangi pemahaman dan keterlibatan mereka dalam proses politik. Hambatan struktural dalam partai politik juga menghambat perempuan untuk mencapai posisi kepemimpinan, dan beban ganda sebagai ibu rumah tangga dan pekerja membuat perempuan sulit untuk berpartisipasi secara penuh dalam politik. Selain itu, kekerasan dan intimidasi terhadap perempuan yang terlibat dalam politik menambah tantangan yang harus dihadapi.n Di sisi lain, penelitian ini juga menemukan beberapa faktor pendorong yang signifikan. Kebijakan afirmatif, seperti kuota gender dalam partai politik dan parlemen, memberikan peluang lebih besar bagi perempuan untuk terlibat dalam politik. Peningkatan pendidikan politik dan kesadaran gender di masyarakat membantu membangun fondasi yang lebih kuat untuk partisipasi politik perempuan. Dukungan dari organisasi non-pemerintah yang berfokus pada pemberdayaan perempuan juga memainkan peran penting dalam memperkuat kapasitas dan motivasi perempuan dalam politik. Perubahan sosial dan budaya yang lebih inklusif, serta jaringan dukungan dan mentorship, membantu perempuan untuk mengatasi hambatan dan berpartisipasi lebih aktif dalam politik. Penelitian ini menyimpulkan bahwa meskipun ada banyak tantangan yang menghambat partisipasi politik perempuan di Indonesia, ada juga banyak faktor pendorong yang dapat dimanfaatkan untuk meningkatkan keterlibatan perempuan dalam politik. Dengan terus memperkuat dukungan bagi partisipasi politik perempuan dan mengatasi hambatan yang ada, Indonesia dapat mencapai kesetaraan gender yang lebih besar dalam politik dan menciptakan lingkungan politik yang lebih inklusif dan berkeadilan bagi semua warga negara.